E-BUSINESS TRANSFORMATION FOR COASTAL FISHERY DEVELOPMENT: ECONOMIC ASSESSMENT OF VALUE-ADDED STRATEGIES IN PULAU KETAM TRADING SYSTEM - Dian Septiana Sari; Annisa Ilmi Faried; Tuan Zamilah Binti Tuan Husain; Widia Br. Ginting (International Journal of Management, Economic and Accounting, 2025)
Digital transformation in coastal fisheries represents a critical pathway toward sustainable economic development and enhanced market competitiveness. This study examines the integration of e-business technologies in traditional fishing communities through comprehensive economic assessment of value-added product strategies in Pulau Ketam, Malaysia. Employing a mixed-methods approach conducted from March to October 2025, this research engaged 385 stakeholders including fishing households (n=165), seafood processing enterprises (n=95), tourism operators (n=55), digital platform users (n=40), and government agencies (n=30). Data collection integrated stakeholder surveys, financial performance analysis, market transaction monitoring, digital adoption assessments, and value chain evaluations. Results demonstrate that e-business adoption generates substantial economic improvements: participating enterprises experienced 63% revenue increase, operating margins improved from 18% to 34%, market reach expanded by 127% beyond traditional boundaries, and value-added product development increased 89%. Digital platforms facilitated direct producer-consumer connections, reducing intermediary dependence by 41% while enabling price premiums of 28-45% for quality-certified seafood products. However, implementation revealed persistent challenges including digital literacy gaps (47% of potential adopters), infrastructure limitations affecting 38% of island businesses, initial capital barriers averaging RM 15,000 per enterprise, and regulatory uncertainties regarding online food safety compliance. This research contributes empirical evidence on digital economy integration in resource-dependent coastal communities while identifying critical success factors for sustainable e-business transformation in developing region fisheries contexts.